Involvement of HO-1 and Autophagy in the Protective Effect of Magnolol in Hepatic Steatosis-Induced NLRP3 Inflammasome Activation In Vivo and In Vitro - Ni-Chun Kuo; Shieh-Yang Huang; Chien-Yi Yang; Hsin-Hsueh Shen; Yen-Mei Lee (Antioxidants, 2020)
Magnolol (MG) is the main active compound of Magnolia officinalis and exerts a wide range of biological activities. In this study, we investigated the effects of MG using tyloxapol (Tylo)-induced (200 mg/kg, i.p.) hyperlipidemia in rats and palmitic acid (PA)-stimulated (0.3 mM) HepG2 cells. Our results showed that Tylo injection significantly increased plasma levels of triglyceride and cholesterol as well as superoxide anion in the livers, whereas MG pretreatment reversed these changes. MG reduced hepatic lipogenesis by attenuating sterol regulatory element-binding protein-1c (SREBP-1c) and fatty acid synthase (FAS) proteins and Srebp-1, Fas, Acc, and Cd36 mRNA expression as well as upregulated the lipolysis-associated genes Hsl, Mgl, and Atgl. Furthermore, MG reduced plasma interleukin-1β (IL-1β) and protein expression of NLR family pyrin domain-containing 3 (NLRP3), apoptosis-associated speck-like protein (ASC), and caspase 1 as well as upregulated nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) and induction of heme oxygenase-1 (HO-1) in hepatocytes of Tylo-treated rats. Enhanced autophagic flux by elevation of autophagy related protein 5-12 (ATG5-12), ATG7, Beclin1, and microtubule-associated protein light chain 3 B II (LC3BII)/LC3BI ratio, and reduction of sequestosome-1 (SQSTM1/p62) and phosphorylation of mTOR was observed by MG administration. However, autophagy inhibition with 3-methyladenine (3-MA) in HepG2 cells drastically abrogated the MG-mediated suppression of inflammation and lipid metabolism. In conclusion, MG inhibited hepatic steatosis-induced NLRP3 inflammasome activation through the restoration of autophagy to promote HO-1 signaling capable of ameliorating oxidative stress and inflammatory responses.